Development of a Cognitive Therapy Module to Enhance Self-Esteem for Youth with Physical Disabilities in Malaysia - Rafidah Aga, Mohd Jaladin; Janet Ann, Fernandez; Ahmad Shamsuri, Muhamad; Aina Razlin, Mohammad Roose; Sapora, Sipon (Faculty of Medicine, Universiti Malaya, 2023)
Youth with physical disabilities may have concerns about their bodily functions and appearance, which do not typically conform to sociocultural norms. A mounting body of research confirmed that physical disability has an adverse impact on self-esteem development. This study was aimed at developing a cognitive therapy module for professional counsellors to help Malaysian youth with physical disabilities enhance their self-esteem. The methodology comprised three stages: (i) self-esteem baseline assessment; (ii) module design and development; and (iii) module evaluation. First, the Rosenberg Self-Esteem Scale was used to collect data from 110 youth with physical disabilities. The results revealed that participants had moderate levels of self-esteem (mean, x̄ = 30.16). This finding highlighted the need to increase the level of self-esteem among youth with physical disabilities. The second stage involved the development of the cognitive therapy module for self-esteem enhancement using Sidek’s model of module development. The third stage involved evaluating the module’s content validity and reliability using Sidek’s model of module development. Findings showed that the therapy module has high content validity and reliability. The overall findings demonstrate that the newly developed module can be applied by professional counsellors to enhance self-esteem among youth with physical disabilities.